Hazardous Implications of Large Format Printing on Graphic Design Operation in Nigeria - Razaq Olatunde Rom Kalilu; Akintola David Abiodun (jfpublisher, 2026)
This study addresses the occupational health implications of hazardous chemical air pollutants in Nigeria's Large Format Printing (LFP) industry. The aim is to raise awareness about the health implications of LFP with a view to proposing measures to safeguard the health of graphic designers during their professional engagement. The methodology employed was a quantitative design, utilizing a typical case sampling strategy to purposively select a single, active LFP press in Somolu for real-time digital air data collection. Samples for TVOCs and HCHO were collected using the Digital Air Quality Detector model VT-6-IN-1 over an 8-hour work shift on five consecutive working days. Based on this exposure time (ET) and exposure frequency (EF), Hazard Index (HI) at non-carcinogenic risks for full-time Operator Graphic Designers (OGDs) was calculated; for Freelance Graphic Designers (FGDs), appropriate ET and EF data were gathered from 150 respondents across 15 LFP shops. Findings reveal that OGDs face serious health challenges, with HI value 2.326 mg/m³ (>1) and exposure levels exceeding NESREA safe standard (TVOC=0.6 mg/m³ and HCHO=0.1 mg/m³). Health implications of this include potential respiratory and neurological injury. For FGDs, HI < 1 indicates safe exposure levels to both pollutants. The study concludes that there is an urgent need to safeguard the health of OGDs in the Nigerian LFP industry, highlights the need for wider free clinical checkups, improved regulatory enforcement, and the implementation of protective measures, such as enhanced ventilation systems, spacious printing workspace, and mandatory use of respiratory equipment with Organic Vapour (OV) cartridge.